Pemeriksaan Kadar Zat Pada Sumber Air Minum Di Desa Sukasari, Pulosari, Pandeglang, Banten - Edy Parwanto; David Tjahyadi; Sisca Sisca (CV. Multi Kreasi Media, 2023)
The villages of Sukasari, Pulosari, Pandeglang, Banten are agricultural areas. Most of the residents of Sukasari Village grow rice in the rice fields, while others are traders, employees and so on. In general, residential areas are located in villages. Most people's houses are permanent, made of brick walls. In general, the village in Sukasari Village at the foot of Mount Karang has a moderate population density (not too dense). The houses in Sukasari Village generally have a yard. The working area of Sukasari Village consists of 3 hamlets, 8 RWs, 26 RTs with a population of 4,239 people. In the work area of Sukasari Village itself, there are only health facilities in the form of 1 midwife practice and 6 posyandu. Pulosari District is one of the sub-districts in Pandeglang Regency. This sub-district has an area of 27.62 km2 and has a population of 28,885 people. Pulosari District consists of 9 (nine) villages, namely Banjarnegara, Kaduhejo, Koranji, Sanghiangdedek, Cilentung, Karyawangi, Sukasari, and Sukaraja. Sukasari Village itself has an area of 4.20 km2. An unbalanced ratio between population and existing health facilities can cause health problems, because if health problems are resolved then the success of an area's development can be said to be successful. Even though we are facing the COVID-19 pandemic, we must not ignore other health problems. Therefore, we will implement a PKM program to check the quality of drinking water for residents in the Sukasari, Pulosari, Pandeglang, Banten Village areas.